Internalisasi Nilai-nilai Keteladanan Orang Tua pada Anak Prasekolah - Rahmadyansyah Rahmadyansyah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Preschool child is a child who must be arranged by the parents in order to establish their personal, one of which may be through the internalization of the values of exemplary parents. Internalization of one's religious values can later be used as a child as the foundation and guidelines in the future. This assessment considers the internalization of the values of exemplary parents on preschool children in the eyes of Islam. Internalization of the values of exemplary parents highly recommended in Islam, because at this stage the children can be nurtured, guided, and directed to be able to know him and his God.